1999
DOI: 10.1083/jcb.146.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Essential Spindle Checkpoint Gene bub1 Cause Chromosome Missegregation and Fail to Block Apoptosis in Drosophila

Abstract: We have characterized the Drosophila mitotic checkpoint control protein Bub1 and obtained mutations in the bub1 gene. Drosophila Bub1 localizes strongly to the centromere/kinetochore of mitotic and meiotic chromosomes that have not yet reached the metaphase plate. Animals homozygous for P-element–induced, near-null mutations of bub1 die during late larval/pupal stages due to severe mitotic abnormalities indicative of a bypass of checkpoint function. These abnormalities include accelerated exit from metaphase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
99
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(108 citation statements)
references
References 68 publications
9
99
0
Order By: Relevance
“…Recent reports demonstrated that loss of APC caused chromosomal missegregation through ␤-catenin͞Wnt-independent mechanisms (36,37) and it is also possible that chromosomal missegregation may cause apoptosis (38,39). Therefore, we cannot exclude an possibility that apoptosis described here might be independent from dysregulation of ␤-catenin͞Wnt signaling.…”
Section: Resultsmentioning
confidence: 39%
“…Recent reports demonstrated that loss of APC caused chromosomal missegregation through ␤-catenin͞Wnt-independent mechanisms (36,37) and it is also possible that chromosomal missegregation may cause apoptosis (38,39). Therefore, we cannot exclude an possibility that apoptosis described here might be independent from dysregulation of ␤-catenin͞Wnt signaling.…”
Section: Resultsmentioning
confidence: 39%
“…For example, Mad2 null mouse causes embryonic lethality and the Mad2 null embryos show high levels of chromosome mis-segregation and apoptosis (Dobles et al, 2000). Deletion of Bub1 in Drosophila is also embryonic lethal (Basu et al, 1999). It is unclear whether the spindle checkpoint is essential for early development of multicellular organisms or whether Mad2, Bub1, and other checkpoint genes have yet unidentified essential noncheckpoint functions.…”
Section: Defective Spindle Checkpoint and Aneuploidymentioning
confidence: 99%
“…These include rod (Karess and Glover 1989; Starr et al, 1998), the MAP kinases ppERK (Shapiro et al 1998; Zecevic et al 1998) and ppMEK (Shapiro et al 1998), and an APC activator protein fizzy (called cdc20/cdh1 in other organisms; Kallio et al 1998). Likewise, the protein kinase polo (Logarinho and Sunkel 1998) and a number of components of the highly conserved spindle assembly checkpoint, including Bub1 (Taylor and McKeon 1997; Taylor et al 1998; Basu et al 1999), Bub3 (Taylor et al 1998; Basu et al 1998; Martinez-Exposito et al 1999), Mad1 (Jin et al 1998; Chen et al 1998), and Mad2 (Waters et al 1998; Chen et al 1996, Chen et al 1998), are transiently kinetochore-bound.…”
Section: Introductionmentioning
confidence: 99%